An invertebrate model for TMEM43-induced arrhythmogenic right ventricular cardiomyopathy (ARVC) type 5. (10th June 2022) - Klinke, N; Reinhardt, M; Ratnavadivel, S; Harten, H; Malmendal, A; Milting, H; Paululat, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DFG Objectives: TMEM43 encodes for a transmembrane protein located in the ER membrane and the nuclear rim. TMEM43 has predicted four transmembrane domains. The missense variant TMEM43 p.S358L is fully penetrant in males and associated with arrhythmogenic right ventricular cardiomyopathy (ARVC) type 5. Even though, TMEM43 is a phyllogenetically conserved protein throughout different species, little is known on the molecular mechanism of the mutation. TMEM43 is highly homologous to the single CG8111 gene in Drosophila melanogaster. The clincal relevant amino acid serine at position p358 is situated in the third transmembrane domain, the same applies to the corresponding amino acid p.S333L in the Drosophila homologue. Here, we established the first invertebrate model to study the pathophysiological effects of the human variant in the Drosophila homologue CG8111. Methods: To investigate the effect of this missense mutation in flies, we introduced the variant CG8111 p.S333L in Drosophila and overexpressed the mutant variant CG8111p.S333L in transgenic flies, either ubiquitously or in a tissue specific manner. Cardiac specific physiological effects of the mutant variant were examined by Semi-automatic Optical Heartbeat Analysis (SOHA) for heart rate, systolic and diastolic interval, fractional shortening and arrhythmicity index. Mutant and wildtype flies were further compared by mass-spectrometry for differentially regulated proteins. Metabolites were analysed by NMR accordingly. Results: Our studies showed that in comparison to the wild type the ubiquitously overexpressed variant leads to lethal effects at pupal stages. Individuals died from reduced food uptake and excessive lipid droplet accumulation in adipocytes. CG8111p.S333L animals up-regulate proteins, involved in fatty acid metabolism pathways. Metabolomic data revealed increased amounts of fatty acids accumulation in mutant versus wild-type animals. Furthermore, heart specific overexpression of CG8111p.S333L was associated with arrhythmias in five week old male flies. Conclusions: CG8111p.S333L overexpression is a lethal genotype in Drosophila. Our data suggest a metabolic dysfunction associated with the mutant form of CG8111p.S333L, which shares pathophysiological characteristics of the human condition in TMEM43 p.S358L carriers.